Effectiveness of Reading Aloud Strategies for Inferential Reading Comprehension Skills and Text Difficulties of Saudi Students at University Level - Sajid, Muhammad Khalid Mehmood; Al Fraidan, Abdullah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Reading comprehension is the ability to process text. It is an essential part of learning for university students. A lot of strategies are used for reading. Among them, reading aloud strategies are vital reading strategies. Saudi Arabia is a country where English is to be spoken as a second language. Due to weak school basal reading, the Saudi students have problem with reading text level where they are failed at university learning material for high-level reading skills such as inferential, evaluative, and critical reading. However; in this study, a survey was distributed among 27 students to know their opinion about the effectiveness of reading aloud strategies for inferential reading comprehension skills and text difficulties of Saudi students at the university level. Convenience sampling was used as both the researchers were from the same place. The study was conducted at the Department of English. College of Arts, King Faisal University, Alhasa. SPSS descriptive statistics were used for analysis by using SPSS version 21. Atlas-ti 8 reports were also used for the elaboration of major themes during the literature review from previous research studies. The findings showed reasonable effectiveness of these strategies. These strategies were also recommended for future research on inferential reading comprehension skills and the solution of difficult text by having the present set up of strategies being used by Saudi university level students.